Fluorous Catalyst Recycling Utilising Highly Fluorinated Zinc Compounds: Ring Opening Polymerisation of e-Caprolactone - BAKER, ROBERT JAMES (Elsevier, 2012)
The synthesis of highly fluorinated zinc carboxylates, [{CF3(CF2)5CH2CH2CO2}2Zn], and alkoxides, [{CF3(CF2)5CH2CH2O}2Zn(OEt2)2] and their use as catalysts for the ring opening polymerisation of ?-caprolactone are described. Quenching the polymerisation reaction with fluorous acids or alcohols regenerates the catalyst which can be recovered by fluorous solvent extractions and the catalytic activity is retained for three cycles. The superior recyclability of the alkoxide to the carboxylate zinc compound is due to the greater partition coefficient between fluorous and organic solvents. Also investigated is the well defined aryloxide compound [(ArO)2Zn(THF)2] which yields very well controlled polymerisation, but cannot be recycled by quenching with a fluorous alcohol.
PUBLISHED
Keywords: Chemistry; Ring Opening Polymerisation; Perfluorinated Alcohols; Zinc Alkoxides